Ecological Momentary Assessment of Bulimia Nervosa: Does Dietary Restriction Predict Binge Eating? - Zunker, Christie (2011)
The purpose of this study was to examine the relationship between caloric restriction (CR) and binge eating (BE) using ecological momentary assessment (EMA). Participants included 133 women with bulimia nervosa (BN) who completed an EMA protocol for 2 weeks. Logistic regression analyses tested whether CR increased the probability of BE episodes. The results revealed that the odds of BE increased on the day that restriction occurred as well as on the following day. In addition, both restriction and BE on one day predicted the likelihood of BE the subsequent day, but restriction for two days prior to the episode failed to add additional information for predicting BE. These findings support the cognitive-behavioral therapy (CBT) model of BN, suggesting that self-reported dietary restriction is predictive of subsequent BE episodes, and that reducing dietary restriction in treatment may lead to improvements in bulimic symptoms.